Novel Combined Immune Deficiency and Radiation Sensitivity Blended Phenotype in an Adult with Biallelic Variations in ZAP70 and RNF168 - Chinn, Ivan K.; Sanders, Robert P.; Stray-Pedersen, Asbjørg; Coban-Akdemir, Zeynep H.; Kim, Vy Hong-Diep; Dadi, Harjit; Roifman, Chaim M.; Quigg, Troy; Lupski, James R.; Orange, Jordan S.; Hanson, I. Celine (Frontiers in Immunology, 2017)
With the advent of high-throughput genomic sequencing techniques, novel genetic etiologies are being uncovered for previously unexplained Mendelian phenotypes, and the underlying genetic architecture of disease is being unraveled. Although most of these ‘mendelizing’ disease traits represent phenotypes caused by single gene defects, a percentage of patients have blended phenotypes caused by pathogenic variants in multiple genes. We describe an adult patient with susceptibility to bacterial, herpesviral, and fungal infections. Immunologic defects included CD8+ T cell lymphopenia, decreased T cell proliferative responses to mitogens, hypogammaglobulinemia, and radiation sensitivity. Whole exome sequencing revealed compound heterozygous variants in ZAP70. Biallelic mutations in ZAP70 are known to produce a spectrum of immune deficiency that includes the T cell abnormalities observed in this patient. Analyses for variants in genes associated with radiation sensitivity identified the presence of a homozygous RNF168 variant of unknown significance. RNF168 deficiency causes RIDDLE syndrome and may account for the radiation sensitivity. Thus, the patient was found to have a novel blended phenotype associated with multilocus genomic variation: i.e., separate and distinct genetic defects. These findings further illustrate the clinical utility of applying genomic testing in patients with primary immunodeficiency diseases.